1997
DOI: 10.1042/bj3270689
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a key regulatory element for the basal activity of the human insulin-like growth factor II gene promoter P3

Abstract: Transcription of the human insulin-like growth factor II (IGF-II) gene is under the control of four promoters (P1-P4) that are differentially active during growth and development. Promoter 3 (P3) is the most active promoter during fetal development as well as in most adult tissues. P3 is also the most active promoter in tumour tissues and cell lines expressing IGF-II. Transient transfections of HeLa and Hep3B cells with truncated promoter constructs revealed that the region between -289 and -183 relative to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1999
1999
2001
2001

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…The following oligonucleotides were provided by Pharmacia (Uppsala, Sweden) : M3upper, 5h-CCGGGTAATCAGGGCCC-CCAGCCCGCACCCCCCGCCCGCTCTTGGC-3h ; M3lower, 5h-CCGAGCCAAGAGCGGGGCGGGGGTGCGGGCTG-GGGGCCCTGATTAC-3h. Other oligonucleotides used, P3-4, P3-4M1 and P3-4M3, were as described previously [6]. The AP-2 consensus oligonucleotide pair 5h-GATCGAACTGAC-CGCCCGCGGCCCGT-3h was purchased from Santa Cruz Biotechnology (Santa Cruz, CA, U.S.A.).…”
Section: Oligonucleotides and Plasmidsmentioning
confidence: 99%
See 2 more Smart Citations
“…The following oligonucleotides were provided by Pharmacia (Uppsala, Sweden) : M3upper, 5h-CCGGGTAATCAGGGCCC-CCAGCCCGCACCCCCCGCCCGCTCTTGGC-3h ; M3lower, 5h-CCGAGCCAAGAGCGGGGCGGGGGTGCGGGCTG-GGGGCCCTGATTAC-3h. Other oligonucleotides used, P3-4, P3-4M1 and P3-4M3, were as described previously [6]. The AP-2 consensus oligonucleotide pair 5h-GATCGAACTGAC-CGCCCGCGGCCCGT-3h was purchased from Santa Cruz Biotechnology (Santa Cruz, CA, U.S.A.).…”
Section: Oligonucleotides and Plasmidsmentioning
confidence: 99%
“…1300 nt upstream of the transcription start site of exon 5 and consists of 70-80 % GC base pairs. Transient transfection assays have revealed that the region between k289 and the transcription start site (j1) supports basal activity in HeLa and Hep3B cells [5,6]. Four elements were identified in this proximal promoter region that were bound by nuclear factors from HeLa cells in footprint analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of WT-1 is associated with overexpression of IGF-2 in Wilms' tumor (20). Other transcription factors that bind the proximal segment of the P3 promoter downstream of position Ϫ288 include p53 (34), the P3-4 cis element-binding proteins (35,36), and AP2 (22, 31) (reviewed in Ref. 37).…”
Section: Discussionmentioning
confidence: 99%
“…A representative autoradiograph of DNA footprint of a total of 2 autoradiographs from 2 experiments with day-5 samples is shown. A labeled DNA ladder was co-run with the DNase-treated samples as a size marker, and the nt sequence of the DNase-protected site was determined by Maxam and Gilbert GϩA track method, as published previously (31,35). A 14-bp region (Ϫ1084/Ϫ1070) with the indicated sequence was specifically protected from DNase 1 digestion (containing the putative P3-D binding site) in the presence of day-5 samples ( lanes 1 and 2).…”
Section: Relative Levels Of Endogenous P3-derived Igf-2 Transcripts Imentioning
confidence: 99%